Progression of C-reactive protein from birth through preadolescence varies by mode of delivery - Alexandra R. Sitarik; Christine C. Johnson; Albert M. Levin; Susan V. Lynch; Dennis R. Ownby; Andrew G. Rundle; Jennifer K. Straughen; Ganesa Wegienka; Kimberley J. Woodcroft; Andrea E. Cassidy-Bushrow (Frontiers Media S.A., 2023)
IntroductionDelivery via caesarean section (C-section) has been associated with an increased risk of childhood chronic diseases such as obesity and asthma, which may be due to underlying systemic inflammation. However, the impact of specific C-section types may be differential, as emergency C-sections typically involve partial labor and/or membrane rupture. Our objectives were to determine if mode of delivery associates with longitudinal profiles of high sensitivity CRP (hs-CRP) -a marker of systemic inflammation-from birth through preadolescence, and to examine if CRP mediates the association between mode of delivery and preadolescent body mass index (BMI).MethodsData from the WHEALS birth cohort (N = 1,258) were analyzed; 564 of the 1,258 children in the cohort had data available for analysis. Longitudinal plasma samples (birth through 10-years of age) from 564 children from were assayed for hs-CRP levels. Maternal medical records were abstracted to obtain mode of delivery. Growth mixture models (GMMs) were used to determine classes of hs-CRP trajectories. Poisson regression with robust error variance was used to calculate risk ratios (RRs).ResultsTwo hs-CRP trajectory classes were identified: class 1 (76% of children) was characterized by low hs-CRP, while class 2 (24% of children) was characterized by high and steadily increasing hs-CRP. In multivariable models, children delivered via planned C-section had 1.15 times higher risk of being in hs-CRP class 2, compared to vaginal deliveries (p = 0.028), while no association was found for unplanned C-section deliveries [RR (95% CI) = 0.96 (0.84, 1.09); p = 0.49]. Further, the effect of planned C-section on BMI z-score at age 10 was significantly mediated by hs-CRP class (percent mediated = 43.4%).ConclusionsThese findings suggest potentially beneficial effects of experiencing partial or full labor, leading to a lower trajectory of systemic inflammation throughout childhood and decreased BMI during preadolescence. These findings may have implications for chronic disease development later in life.